Prevalence of Escherichia Coli, Salmonella Sp, Staphylococcus Aureus Bacteria in Chicken Meat of Traditional Market Surabaya City - Ulfa Dwi Karisma; Nurul Wiqoyah; Suhintam Pusarawati (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Foodborne disease is a disease caused by contaminated food. Chicken meat is very susceptible to contamination by bacteria. Escherichia coli, Salmonella sp, and Staphylococcus aureus are types of bacteria found in chicken meat. The purpose of this study was to see how many Escherichia coli, Salmonella sp, and Staphylococcus aureus colonies in raw chicken meat in traditional markets in Surabaya City. The research sample used was 30 samples of chicken meat taken in 5 traditional markets in Surabaya. Six chicken meat sellers were taken with 1 sample and put in the sterile tube from each market. The test was carried out using the Total Plate Count (TPC) method. The TPC test results showed that all samples were contaminated with E. coli, with the most colony being 2.2X10-7 CFU/g while the minor colony was 5X10-4 CFU/g. There are two samples contaminated with Salmonella sp, in the G market and the W market, with code D6 4.7X10-6 CFU/g and code E5 1X10-6 CFU/g. Meanwhile, S. aureus was only found in the W market with sample codes E1 & E6, and each sample had a colony of 2.7X 10-7 CFU/g and 2X10-5 CFU/g.